Book Reviews (The Muslim world, 1955)
Book reviews in this article: The Middle East - A Political and Economic Survey. By the Royal Institute of International Affairs Oil in the Middle East: Its Discovery and Development. By Stephen Helmsley Longrigg The Structure of Spanish History. By Américo Castro Glimpses of Iqbal'r Mind and Thought. By H. H. Bilgrami Under Three Flags. By Stephen Neill Beyond Romance, A true story from the hurt of India. By F. Balph Revolution In Missions. By Willis Church Lamott Islam in India and theMiddle East. By S. M. Ahmed Essentials of Modern Turkish By Herman H. Kreider Report of the Court of Inquiry into the Panjab Disturbances of 1953. Lahore